2020
DOI: 10.3390/agronomy10020216
|View full text |Cite
|
Sign up to set email alerts
|

Tipburn Incidence and Ca Acquisition and Distribution in Lisianthus (Eustoma grandiflorum (Raf.) Shinn.) Cultivars under Different Ca Concentrations in Nutrient Solution

Abstract: Tipburn (calcium (Ca) deficiency disorder) is a major problem in the production of lisianthus cultivars. However, few studies have investigated the influence of different Ca concentrations in nutrient solution on tipburn incidence and Ca acquisition and distribution. Thus, it remains unclear why some cultivars exhibit tipburn under high Ca concentrations. To address this, we used three lisianthus cultivars ‘Azuma-no-Kaori’ (AK), ‘Celeb Wine’ (CW), and ‘Voyage Yellow’ (VY) and compared tipburn incidence and Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…By contrast, RW was considered a tipburn-semi-sensitive cultivar, as the occurrence of tipburn could be prevented by supplying high concentrations of Ca in the nutrient solutions. This result was consistent with that reported in Azuma-no-kanori (AK) [13]. VP, in which the tipburn incidence was 100%, was considered a tipburn-sensitive cultivar.…”
Section: Severity and Incidence Of Tipburn Under Different Concentratsupporting
confidence: 92%
See 4 more Smart Citations
“…By contrast, RW was considered a tipburn-semi-sensitive cultivar, as the occurrence of tipburn could be prevented by supplying high concentrations of Ca in the nutrient solutions. This result was consistent with that reported in Azuma-no-kanori (AK) [13]. VP, in which the tipburn incidence was 100%, was considered a tipburn-sensitive cultivar.…”
Section: Severity and Incidence Of Tipburn Under Different Concentratsupporting
confidence: 92%
“…In rice [16] and barley [17], it has been reported that a high K concentration inhibits Ca uptake. Therefore, a high content ratio of K in the nutrient solution in our previous experiments [10][11][12][13] may have prevented Ca acquisition and distribution in some lisianthus cultivars. It is necessary to investigate the relevance of Ca and K concentrations in lisianthus cultivars.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations